Design and Initial Testing of Acoustically Stimulated Anaerobic Digestion Coupled with Effluent Aeration for Agricultural Wastewater Remediation - John H. Loughrin; Philip J. Silva; Stacy W. Antle; Nanh Lovanh; Matias B. Vanotti; Karamat R. Sistani (AgriEngineering)
The construction of an anaerobic digester coupled with post-digestion low-level aeration for agricultural wastewater treatment is described. The digester employs underwater speakers to accelerate the anaerobic digestion process while retaining solids to reduce the strength of the effluent. The effluent is sent to a holding tank and fed at a low flow rate to an aeration tank to effect partial nitrification of the wastewater. The outlet of this tank is sent to a settling tank to retain biomass that developed in the aeration tank, and the effluent is sent to a small constructed wetland to further reduce wastewater nitrogen and phosphorus. The wetland was planted with the broadleaf cattail, Typha latifolia, and hence led to the formation of a retention basin. The system has reduced energy consumption due to the use of underwater sonic treatment and low-level aeration that is not designed to achieve full nitrification/denitrification but rather to achieve a mixture of ammonium, nitrite, and nitrate that might foster the development of a consortium of organisms (i.e., nitrifiers and Anammox bacteria) that can remediate wastewater ammonium at low cost. The system is meant to serve as a complex where various technologies and practices can be evaluated to improve the treatment of agricultural wastewater. Preliminary data from the system are presented.